The Impact of Post-Analytical Tools on New York Screening for Krabbe Disease and Pompe Disease - Monica M. Martin; Ryan Wilson; Michele Caggana; Joseph J. Orsini (MDPI AG, 2020)
New York uses a two-tier assay to screen newborns for Krabbe disease and Pompe disease. Individual enzyme activities are measured in the first-tier, and specimens from newborns with low activity are reflexed to second tier Sanger sequencing of the associated gene. Using only this two-tiered approach, the screen positive and false positive rates were high. In this study, we added an additional step that examines the activity of four additional lysosomal enzymes. Results for all enzymes are integrated using the multivariate pattern recognition software called Collaborative Laboratory Integrated Reports (CLIR) to assess the risk for disease. Results after one year of screening using the new algorithm are compared to the prior year of screening without consideration of the additional enzymes and use of CLIR. With CLIR the number of babies referred for Krabbe disease was reduced by almost 80% (from 48 to 10) and the number of babies referred for Pompe disease was reduced by almost 32% (22 to 15).